A multicentre, randomised, double-blind, phase II study to evaluate the tolerability of an induction dose escalation of everolimus in patients with metastatic breast cancer (DESIREE) - Schmidt, M.; Lübbe, K.; Decker, T.; Thill, M.; Bauer, L.; Müller, V.; Link, T.; Furlanetto, J.; Reinisch, M.; Mundhenke, Christoph; Hoffmann, O.; Zahn, M. O.; et al. (ESMO Open, 2022)
Background: Stomatitis is one of the main reasons to discontinue everolimus in patients with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2–) metastatic breast cancer (mBC). To decrease stomatitis and subsequently early treatment discontinuations or dose reductions, the DESIREE trial investigated the use of a stepwise dose-escalation schedule of everolimus (EVE esc). Patients and methods: DESIREE is a phase II, multicentre, randomised, double-blind, placebo-controlled trial in patients with HR+/HER2– mBC and progression/relapse after nonsteroidal aromatase inhibitor treatment. Patients were randomised to EVE esc (2.5 mg/day, week 1; 5 mg/day, week 2; 7.5 mg/day, week 3; 10 mg/day, weeks 4-24) or everolimus 10 mg/day (EVE 10mg) for 24 weeks plus exemestane. The primary endpoint was the incidence of stomatitis episodes grade ≥2 within 12 weeks of treatment. The secondary endpoints included toxicity, relative total dose intensity (RTDI) and quality of life (QoL). Results: A total of 160 patients were randomised and 156 started treatment (EVE esc: 80; EVE 10mg: 76). The median age of patients was 64 years (range 33-85), 56.3% patients in the EVE esc arm versus 42.1% in the EVE 10mg arm had liver metastasis (P = 0.081) and 62.5% versus 51.3% received over one metastatic therapy line (P = 0.196). Within 12 weeks, the incidence of stomatitis episodes grade ≥2 was significantly lower in the EVE esc arm compared with the EVE 10mg arm (28.8% versus 46.1%; odds ratio 0.47, 95% confidence interval 0.24-0.92; P = 0.026). Toxicity was in line with the known safety profile without new safety concerns. The median RTDI was 91.1% in the EVE esc arm versus 80.0% in the EVE 10mg arm (P = 0.329). Discontinuation rate in the first 3 weeks was 6.3% versus 15.8%, respectively (P = 0.073). QoL was comparable between the two treatment arms. Conclusions: A dose-escalation schema of everolimus over 3 weeks can be successfully used to reduce the incidence of high-grade stomatitis in the first 12 weeks of treatment in patients with HR+/HER2– mBC. Trial registration: ClinicalTrials.gov NCT02387099; https://clinicaltrials.gov/ct2/show/NCT02387099
CRIS-Team Scopus Importer:2022-11-25
Keywords: everolimus; exemestane; metastatic breast cancer; stomatitis